2015
DOI: 10.3109/00016489.2014.999876
|View full text |Cite
|
Sign up to set email alerts
|

Nasal symptomatology, obstruction, and paranasal sinus opacity in patients with chronic obstructive pulmonary disease

Abstract: In the COPD group, there was a higher occurrence of nasal symptoms and pathological findings on nasal endoscopy compared with the control group. The overall nasal airflow was higher in the control group (compared with COPD patients) and the overall nasal resistance was higher in the COPD group (compared with controls). Pathological opacity of one or more sinuses was confirmed in 38% of COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…The frequency of abnormal CT findings in 21% was lower compared to the results of Kelemence et al (64%), probably due to the fact that a higher cut-off for an abnormal CT scan was used in our study (0 in Sichtelidis et al vs. > 4.26 in our study) [12]. Also Celakovsky et al found a higher rate of abnormal CTs with 38% even though they excluded patients with sino-nasal surgery, which was frequent in our cohort [15]. Also in this case they used a different cut-off compared to our study as they rated CTs to be abnormal if there was an opacity of one or more sinuses.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The frequency of abnormal CT findings in 21% was lower compared to the results of Kelemence et al (64%), probably due to the fact that a higher cut-off for an abnormal CT scan was used in our study (0 in Sichtelidis et al vs. > 4.26 in our study) [12]. Also Celakovsky et al found a higher rate of abnormal CTs with 38% even though they excluded patients with sino-nasal surgery, which was frequent in our cohort [15]. Also in this case they used a different cut-off compared to our study as they rated CTs to be abnormal if there was an opacity of one or more sinuses.…”
Section: Discussioncontrasting
confidence: 71%
“…5,8 In summary even though most studies indicated an association between COPD and upper airway disease such as CRS the evidence remains inconclusive and lacks a comprehensible assessment, such as sinonasal imaging or a control group. 12,14,15 To investigate the prevalence of CRS in COPD and its impact on COPD outcomes we examined symptoms of CRS in COPD patients and a control group using a structured questionnaire, SNOT-20 and computed tomography (CT) of the para-nasal sinuses. We hypothesized that the prevalence of CRS is higher in the COPD compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is in line with studies looking at chronic rhinosinusitis, which is defined by established criteria [27]. Cross-study comparisons are difficult due to different definitions of UAS and the use of different questionnaires [28][29][30]. Whereas the SNOT22 is a validated and commonly used questionnaire, it was not developed to screen for UAS but to assess patients for surgery in chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 89%
“…Apparently the sensation of nasal obstruction in asthmatics is different from controls despite being in the same PNIF group . Finally, evaluating nasal resistances by means of RM in subjects with COPD, a very recent prospective study found that these patients have higher nasal resistances compared to controls also .…”
Section: The Relation Between Nasal Flow and Patency Measurements Andmentioning
confidence: 97%